THE INFLUENCE OF CLEAR SHAMPOO ADVERTISEMENTS ON PURCHASE DECISIONS (CASE STUDY ON CLEAR SHAMPOO ADVERTISING CELEBRITIES ENDORSER: AGNES MONICA) - Oktavia Anna Rahayu (International Journal Multidisciplinary Science, 2023)
Increasingly fierce competition in producing products requires producers to carry out the right strategy so that their products can survive in the market. One of the ways to do this is to carry out promotions using celebrity endorsers as good message distributors. This study used multiple linear regression tests to determine the effect of celebrity endorser: Agnes Monica on Clear shampoo advertisements on consumer purchasing decisions. From the results of the partial test of the four variables studied, only attractiveness and power variables have an effect. That means the respondents rated Agnes Monica as a celebrity endorser capable of being inspirational and charismatic who was able to increase purchasing decisions of an advertised product, namely Clear shampoo.The variables of visibility and credibility have no effect on consumer purchasing decisions. From these results we can see that consumer purchasing decisions are not only influenced by how popular a celebrity endorser is, but also by the attractiveness and power of the endorser to make consumers confident in making purchasing decisions on advertised products.From the results of the simultaneous test of the four variables studied, it turns out that overall the variables of visibility, credibility, attractiveness and power influence consumer purchasing decisions. That means Agnes Monica as a celebrity endorser has popularity and is able to communicate advertised products, as well as being an inspiration and idol for others.